In pieces eaudiobook - Field, Sally (2018)
In this haunting memoir, an American icon tells her story of a challenging childhood, the craft that helped her find her voice, and a powerful legacy that shaped her journey as a daughter and a mother. One of the most celebrated and beloved actors of our time, Sally Field has an infectious charm that has captivated the nation for more than five decades. From the dazzling complexity of Sybil , to the Academy Award-winning performances in Norma Rae and Lincoln , Field has stunned audiences time and time again with her artistic range and emotional acuity. Yet there is one character who always remained hidden: the shy and anxious little girl within. With raw honesty, humility, and authenticity her fans have come to expect, Field brings readers behind-the-scenes for not only the highs and lows of her star-studded early career in Hollywood, but deep into the truth of her lifelong relationships–including her complicated love for her own mother. Powerful and unforgettable, In Pieces is an inspiring account of life as a woman in the second half of the twentieth century.